On the possibility of applying achievement goal theory in competitive sports - Kuczek, P. (Human Movement, 2013)
Purpose: There exist numerous empirical proofs as well as theoretical bases showing that task motivational orientation and task climate allow students and athletes to function better and be more efficient. What is not certain is whether the same applies to athletes competing at the professional level. The aim of this study was to analyze whether task orientation and task-oriented climate help professional athletes avoid experiencing high levels of anxiety, thereby providing a favorable foundation for performance in high-level competition. Methods: Basketball players from the Polish II League (amateur) and Extraleague (professional) were surveyed. Motivational orientation, motivational climate, and anxiety levels were measured by the Perception of success Questionnaire (POSQ), Perception of significant Others` sport success criteria Questionnaire (PSOSSCQ), and Sport Anxiety scale (SAS), respectively. Results. The reliability of the research tools on a Polish population was confirmed. Motivational climate was associated with motivational orientation; task orientation and a task-oriented climate were found to not reduce anxiety levels. Conclusions. The results do not confirm the application of achievement goal theory in high-level competitive sports.